2006
DOI: 10.1056/nejmoa066139
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Intervention for Persistent Occlusion after Myocardial Infarction

Abstract: BACKGROUND-It is unclear whether stable, high-risk patients with persistent total occlusion of the infarct-related coronary artery identified after the currently accepted period for myocardial salvage has passed should undergo percutaneous coronary intervention (PCI) in addition to receiving optimal medical therapy to reduce the risk of subsequent events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
408
3
31

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 646 publications
(452 citation statements)
references
References 39 publications
10
408
3
31
Order By: Relevance
“…Patients without ongoing chest pain or inducible ischaemia, presenting between 3 and 28 days with persistent coronary artery occlusion, did not benefit from PCI [90,91]. Thus, in patients presenting days after the acute event with a fully developed Q-wave MI, only patients with recurrent angina and/or documented residual ischaemia and proven viability in a large myocardial territory are candidates for mechanical revascularization.…”
Section: Delayed Percutaneous Coronary Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients without ongoing chest pain or inducible ischaemia, presenting between 3 and 28 days with persistent coronary artery occlusion, did not benefit from PCI [90,91]. Thus, in patients presenting days after the acute event with a fully developed Q-wave MI, only patients with recurrent angina and/or documented residual ischaemia and proven viability in a large myocardial territory are candidates for mechanical revascularization.…”
Section: Delayed Percutaneous Coronary Interventionmentioning
confidence: 99%
“…Following the negative results of two RCTs addressing the usefulness of opening occluded culprit coronary arteries in the early post-MI phase [90,91,211], there is some confusion regarding the indications for PCI in 'chronic' total occlusions. In asymptomatic patients within 3 28 days after MI, the OAT trial showed no survival advantage from PCI and less recurrent MI with the conservative approach [90,211]. The results of OAT do not necessarily pertain to CTOs.…”
Section: Specific Lesion Subsetsmentioning
confidence: 99%
“…Studies have shown that PCI elective prescription for an occluded coronary artery within one to 28 days after the AMI occurrence in stable patients, did not provide any benefit greater than that offered by medical therapy consisting of aspirin, betablockers, angiotensin converting enzyme inhibitors and statins in preserving left ventricular contractile function and new cardiovascular events 22,23 . The population served in HSPE-FMO, IAMSPE is characterized by the prevalence of elderly patients and patients over 70 years old account for approximately 30.0% of the admissions information of great importance since such patients are often excluded from clinical trials 34 .…”
Section: Galon Et Al Coronary Artery Disease In the Elderlymentioning
confidence: 99%
“…2 This was a National Heart, Lung, and Blood Institute-supported trial. This trial was similar to the DECOPI trial, but more patients were enrolled, such as 1,082 randomized to PCI/stent plus medical therapy and 1,084 randomized to medical therapy.…”
Section: The Occluded Artery Trialmentioning
confidence: 99%